Presenting symptoms as prognostic measures of mental health recovery among service members with concussion - Remigio-Baker, Rosemay A.; Hungerford, Lars D.; Ettenhofer, Mark L.; Barnard, Lori L.; Babakhanyan, Ida; Ivins, Brian; Stuessi, Keith; Monasterio, Carlos Diego J.; Bailie, Jason M. (Frontiers in Neurology, 2023)
Background Comorbid mental illness may negatively impact recovery from concussion. This study evaluated whether the level of symptom clusters at clinic intake contribute to poor mental health recovery in concussed patients during treatment, which may in turn serve as a target intervention. Objective The objective of this study is to examine the association between the level of initial symptoms and mental health symptoms among service members with concussion. Methods Data were obtained from 483 active duty service members treated in interdisciplinary treatment programs for traumatic brain injury, all of which were concussions. Pre-treatment symptom clusters included self-reported hyperarousal, dissociation/depression, cognitive dysfunction/headache and neurological symptoms. The outcomes, clinically-relevant decreases in depressive symptoms (assessed by the 8-item Patient Health Questionnaire, PHQ-8) and PTSD symptoms (assessed by the PTSD Checklist for DSM-5, PCL-5), were defined as a decrease in PHQ-8 > 5 and PCL-5 > 7, respectively. Poisson regression with robust error variance was used to evaluate the relationship between the level of each symptom cluster and clinically-relevant decrease in outcomes. Results Participants with higher (vs. lower) levels of pre-treatment hyperarousal and dissociation/depression symptom cluster were less likely to improve in depressive and PTSD symptoms during treatment. The level of cognitive/headache and neurological symptom clusters were not significantly associated with any symptom changes. Conclusion These findings support the need for individualized treatment for symptoms identified and treated after determining concussion history, with particular attention to high levels of hyperarousal and dissociation/depression prior to treatment.